2
$\begingroup$

Consider the integral \begin{align} I = \int_{0}^{1} \frac{ \ln^{2}x}{(x^{2} - x + 1)^{2}} \, dx. \end{align} It is speculated that the value is \begin{align} I = \frac{10 \, \pi^{3}}{3^{5} \, \sqrt{3}} - \zeta(2) + \frac{1}{18} \, \left( \psi^{(1)}\left(\frac{1}{3}\right) + \psi^{(1)}\left(\frac{1}{6}\right) \right). \end{align} Is it possible to obtain a demonstration of this result?

$\endgroup$
  • $\begingroup$ Are you sure you got that right? Numerically, the integral is $2.462556187$ but your expression is $1.725869676$. $\endgroup$ – Robert Israel Jul 2 '15 at 0:49
  • 1
    $\begingroup$ Ah, the $10$ should be $20$. $\endgroup$ – Robert Israel Jul 2 '15 at 1:55
3
$\begingroup$

Write $\dfrac{1}{(x^2-x+1)^2}$ as a Taylor series $\sum_{j=0}^\infty a_j x^j$. The coefficients can be written as $$ a_j = \dfrac{j+1}{3} b_j + \dfrac{2}{3} c_j $$ where $b_j$ repeats $1,2,1,-1,-2,-1,\ldots$ for $j = 0,1,2,\ldots$ while $c_j$ repeats $1,1,0,-1,-1,0,\ldots$, both with period $6$. Now $$\int_0^1 \log^2(x)\; x^k\; dx = \dfrac{2}{(k+1)^3}$$ so your integral becomes $$ \dfrac{2}{3} \sum_{j=0}^\infty \dfrac{b_j}{(j+1)^2} + \dfrac{4}{3} \sum_{j=0}^\infty \dfrac{c_j}{(j+1)^3} $$ For $j \equiv 0 \mod 6$ we have $b_j = 1$, $c_j = 1$ and the contribution is $$ \eqalign{\dfrac{2}{3} \sum_{i=0}^\infty \dfrac{1}{(6i+1)^2} + \dfrac{4}{3} \sum_{i=0}^\infty \dfrac{1}{(6i+1)^3} &= \dfrac{1}{54} \sum_{i=0}^\infty \dfrac{1}{(i+1/6)^2} + \dfrac{1}{162} \sum_{i=0}^\infty \dfrac{1}{(i+1/6)^3}\cr & = \dfrac{\psi^{(1)}(1/6)}{54} + \dfrac{\psi^{(2)}(1/6)}{324}} $$ Similarly we can compute the contributions for $j = 1$ to $5 \mod 6$. I get (with Maple's help) a total of $$ \dfrac{\pi^2}{162} + {\frac {\psi^{(1)} \left(1/6 \right) }{54}}-{\frac {\psi^{(2)} \left(1/6 \right) }{324}}+\dfrac{\psi^{(1)} \left( 1/3 \right)}{27} -{\frac {\psi^{(2)} \left( 1/3 \right) }{324}}-{\frac {\psi^{(1)} \left( 2/3 \right) }{54}}+{\frac {\psi^{(2)} \left( 2/3 \right) }{324}}-\dfrac{ \psi^{(1)} \left(5/6 \right)}{27} +{\frac {\psi^{(2)} \left( 5/6 \right) }{324}} $$ Using the reflection identities for $\psi$ this becomes $$ \dfrac{\psi^{(1)}(1/6)}{18} + \dfrac{\psi^{(1)}(1/3)}{18} - \dfrac{\pi^2}{6} +{\frac {20\,{\pi }^{3}\sqrt {3}}{729}} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.